Evaluation of paranasal sinus diseases by computed tomography and its histopathological correlation - Sarabpreet Singh Kanwar; Mukta Mital; Prashant K Gupta; Sonal Saran; Nishtha Parashar; Akanksha Singh (Wolters Kluwer Medknow Publications, 2017)
Context: Paranasal sinus (PNS) diseases affect a wide range of population and include a broad spectrum of diseases ranging from inflammatory conditions to neoplasms, both benign and malignant. Since their clinical assessment is fraught by the surrounding bony structures; diagnostic radiology is of paramount importance. Aims: This study aims to evaluate the spectrum of PNS diseases on computerized tomography (CT) and correlate their clinical and histopathological findings. Settings and Design: A prospective study one at tertiary care hospital. Subjects and Methods: All patients underwent noncontrast CT (NCCT) of PNSs on multi-detector CT Philips Ingenuity Core 128 multi-slice unit and subsequently underwent functional endoscopic sinus surgery by Hopkins Rod 0° 4 mm endoscope with camera system after that procured specimen was sent for its histopathology. This histopathological diagnosis was correlated with CT diagnosis. Their clinical significance was analyzed statistically. Statistical Analysis Used: All obtained data were compiled in tabulated manner and results were expressed as mean ± standard deviation for the statistical analysis, using Statgraphics Centurion (Version 6.2), Statpoint Technologies, Inc. Virginia 2019. Results: A maximum number of patients were in the age group of 21-30 years. The predominant chief presenting complaint was a headache, followed by nasal discharge. The most common CT diagnosis was chronic sinusitis. Maxillary sinus was the most frequently involved sinus and most common CT inflammatory pattern observed was of sinonasal polyposis. Conclusions: This study proved that CT is an excellent imaging modality for evaluating the normal anatomy, variants, and pathologies of the PNSs with a potential pitfall for the diagnosis of fungal sinusitis.